2010
DOI: 10.1007/s11164-010-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of high coercivity Nd23Dy10Fe64TM2B1 sintered magnets by a convergent heat treatment

Abstract: The magnetic property of Nd 23 Dy 10 Fe 64 TM 2 B 1 alloy was investigated by the convergent heat treatment at 350 to 450°C with the heating/cooling rate of 10°C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For example, the addition of Dy, Co and Al improved the coercivity and thermal stability, but significantly decreased the Br and (BH) max [3,5]. Studies have also shown that post-sintering heat treatment can greatly enhance the coercivity of sintered Nd-Fe-B magnets [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the addition of Dy, Co and Al improved the coercivity and thermal stability, but significantly decreased the Br and (BH) max [3,5]. Studies have also shown that post-sintering heat treatment can greatly enhance the coercivity of sintered Nd-Fe-B magnets [6][7][8].…”
Section: Introductionmentioning
confidence: 99%